Pengaruh Bulu Sikat Gigi Rata Dengan Bulu Sikat Gigi Zig-Zag Dari Bahan Nilon Terhadap Penurunan Plak Pada Anak Perempuan Usia 12 Tahun Dengan Metode Menyikat Gigi Secara Horisontal - Nurul Fauziah; Iwa Sutardjo (Universitas Muhammadiyah Yogyakarta, 2007)
Plaque is a layer with width 2mm contains at least 70% of bacteria which can can’t be cleaned and removed by usual gargling. The effective and easiest way to remove plaque is brushing. Nowadays, there are many kinds of toothbrush type available in the market. Flat bristle and zig-zag bristle are common for toothbrush selling in the market. The experiment is belongs to clinical experiment object to 20 girl kids which are I2 year old, with ﬂat bristle and zig-zag bristle as independent variable and plaque as dependent variable. In this experiment, we have used PH index for counting amount of plaques. The research got the positive signiﬁcant differences (p0,05) of plaque removal using zig-zag bristle toothbrush than ﬂat bristle toothbrush, in labial, palatal, buccal, or lingual area. In the whole tooth area which examined, the average value of zigzag bristle toothbrush is bigger than flat bristle toothbrush. It means that zig-zag bristle toothbrush is more effective in plaque removal than flat bristle toothbrush.